The female of Epipleoneura spatulata Rácenis, 1960 (Odonata: Protoneurinae) - Vilela, Diogo Silva; Neiss, Ulisses Gaspar; Koroiva, Ricardo; Guillermo-Ferreira, Rhainer; Hamada, Neusa (Zootaxa, 2020)
Here we describe the hitherto unknown female of Epipleoneura spatulata Rácenis, 1960 and present a table of characters (all illustrated) to distinguish it from other known congeneric females. We suggest that the main diagnostic character of the female of E. spatulata is the shape of posterior margin of prothorax, which is flat medially with smoothly curved erect lateral projections.